2009
DOI: 10.1093/schbul/sbp034
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Dysfunction in Bipolar and Schizophrenia Spectrum Disorders Depends on History of Psychosis Rather Than Diagnostic Group

Abstract: Our findings suggest that neurocognitive dysfunction in bipolar and schizophrenia spectrum disorders is determined more by history of psychosis than by Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition) diagnostic category or subtype, supporting a more dimensional approach in future diagnostic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
263
2
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(291 citation statements)
references
References 41 publications
19
263
2
7
Order By: Relevance
“…However, Harkavy-Friedman et al (2006) did not find significant differences between BD I and BD II patients with a depressive episode and suicide attempts and HCs. Simonsen et al (2011) investigated whether neurocognitive dysfunction depends more on the history of psychosis or the diagnostic subtype and found that the latter only had significant main effect on two verbal recall measures, whereas history of psychosis influenced all subscores.…”
Section: Verbal Memorymentioning
confidence: 99%
“…However, Harkavy-Friedman et al (2006) did not find significant differences between BD I and BD II patients with a depressive episode and suicide attempts and HCs. Simonsen et al (2011) investigated whether neurocognitive dysfunction depends more on the history of psychosis or the diagnostic subtype and found that the latter only had significant main effect on two verbal recall measures, whereas history of psychosis influenced all subscores.…”
Section: Verbal Memorymentioning
confidence: 99%
“…2,5,8 Nevertheless, the mechanisms underlying this association are not well understood. 1,2,9 Cognitive dysfunctions are central to schizophrenia and BD, [10][11][12][13] and recent data suggest that the cognitive decline begins in childhood. 14,15 The cognitive impairments that are typically shared by patients with schizophrenia and BD 12,16,17 have a genetic basis, 18,19 which does not preclude environmental influences from further impacting the developmental trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects overlap between affective and psychotic disorders in genetic ) and environmental risk factors (Weiser et al 2005), as well as in underlying endophenotypes, for example (neuro)cognitive, social and emotional dysfunctions (Weiser et al 2005;Hill et al 2009;Simonsen et al 2011). The overlap in diagnostic constructs has important implications for both research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%